Pengembangan Bahan Ajar Interaktif Menggunakan Liveworksheet Terhadap Materi Keanekaragaman Hayati - Made Cristiana; Ida Bagus Putu Arnyana; I Made Sutajaya; Desak Made Citrawathi; Ida Ayu Purnama Bestari (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This research and development study aimed to design and analyze the validity and practicality of interactive teaching materials using Liveworksheets for the topic of biodiversity, intended for 10th-grade high school students. The study employed the 4D (Four-D) model, comprising four stages: define, design, develop, and disseminate. The dissemination stage was conducted on a limited scale, covering only validation testing, practicality testing, and product packaging, as the research focused primarily on the development process and the initial evaluation of the resulting media. Validity testing was conducted by two subject matter experts and two media experts, with results calculated using the Gregory formula. The assessment results indicated that the Gregory Validity Coefficient (KVG) for both subject matter and media experts reached a score of 1 (one), placing the materials in the "highly valid" category. Practicality testing was subsequently conducted at SMA Negeri 1 Sawan, involving two Biology teachers and 32 10th-grade students in a large-group trial. Analysis revealed practicality levels of 85% from the teachers and 91.15% from the students, both falling into the "highly practical" category. Based on these findings, it is concluded that the interactive teaching materials using Liveworksheets for the biodiversity topic are highly valid and highly practical for use in classroom learning by 10th-grade high school students.